Analysis of lead pollution control in anode slime micromorphology evolution induced by Mn2+ ions for cleaner production of zinc electrolysis. (15th May 2021) - Zhang, Chen-Mu; Shi, Yao; Jiang, Lin-Hua; Hu, Ying-Yan; Li, Qiang; Li, Hui-Quan
Abstract: To explore cleaner production technologies to control lead (Pb) pollution caused by anode slime is a challenging issue for zinc electrolysis industry. The influence of manganese ions (Mn 2+ ) on anode slime microtopography evolution and its relationship with Pb release of lead-based anodes was studied in detail. Scaling analysis was first introduced to quantitatively evaluate anode slime micromorphology evolution, and reveal its intrinsic growth mechanism induced by Mn 2+ ions through parameterizing the morphological information of atomic force microscopy (AFM). Low Mn 2+ concentrations (1–3 g/L) were found to induce the initial anode slime micromorphology to be compact, of which growth was revealed to be controlled by surface diffusion alone corresponding the exponent α  = 0.95. Results of Scanning electron microscopy (SEM ) and inductively coupled plasma mass spectrometry (ICP-MS) extended to 240 h of electrolysis supported that anode slime micromorphology evolution in this case could contribute to inhibiting lead pollution, and the release of Pb from lead-based anodes into electrolytes was controlled at 0.5 mg/L. As the Mn 2+ concentration increased to 10 g/L, the initial anode slime micromorphology was found that the evolution trend from smooth to rough. And the changes in the growth mechanism from the surface diffusion control to volume or bulk diffusion control were found, which appeared as two distinct hierarchical features corresponding to static exponents α  = 0.92 and α'  = 0.55. In this case, excess Mn 2+ ions inducing deteriorated anode slime micromorphology evolution was revealed, and large fluctuations of Pb 2+ concentrations (1.2–1.5 mg/L) in electrolytes with prolonged electrolysis suggested that it was inadequate in inhibiting Pb 2+ release. Scaling analysis for in-depth analysing and predicting the evolution trend of anode slime microtopography induced by Mn 2+ ions has been established, thus new insights gained herein can contribute to exploring approaches to control lead pollution by cleaner production technologies during zinc electrolysis. Graphical abstract: Image 1 Highlights: Scaling analysis based on AFM is established to quantitatively evaluate anode slime microtopography induced by Mn 2+ ions. The surface diffusion growth mechanism was revealed to be the key of low Mn 2+ concentrations to control Pb 2+ release. The change of growth mechanism in volume diffusion was found to induce the deterioration of anode slime micromorphology.